Analysis of Anti-Corruption Value Socialization in Building Integrity Among 6th Grade Elementary School Students - Siti Muniroh (ILAW, 2024)
This study analyzes the socialization of anti-corruption values in building integrity among 6th grade elementary school students. The research aims to examine how values such as honesty, responsibility, discipline, and fairness are introduced and internalized through school-based learning and habituation practices. A qualitative descriptive method with a case study approach is employed, using data collection techniques including observation, interviews, and documentation. The findings show that the socialization of anti-corruption values is effective when integrated into daily learning activities and supported by teacher modeling and participatory learning methods. Students demonstrate improved understanding and behavioral consistency when values are contextualized in real-life school situations. However, challenges remain in ensuring consistency between school-based value education and the broader social environment. The study concludes that continuous and collaborative efforts between schools, teachers, and society are essential for strengthening students’ integrity through anti-corruption value socialization.